Targeted metabolomics suggests a probable role of the FTO gene in the kynurenine pathway in prediabetes - Chailurkit, La-or; Chanprasertyothin, Suwannee; Thongmung, Nisakron; Sritara, Piyamitr; Ongphiphadhanakul, Boonsong (PeerJ (San Francisco, CA), 2022)
Genome-wide association studies have identified the alpha-ketoglutarate dependent dioxygenase gene (FTO) as the first susceptibility gene of obesity. In the present study, we utilized targeted metabolomics in an attempt to further elucidate mechanisms underlying the action of the FTO gene. This study was part of a health survey of employees of the Electricity Generating Authority of Thailand ( = 79, 10 female and 69 male). Targeted metabolomics was performed by liquid chromatography-mass spectrometry using Biocrates AbsoluteIDQ-p180 kit. Genotyping of FTO rs9939609 was performed by real-time PCR (TaqMan™ MGB probes). Using OPLS-DA variable importance in projection (VIP), tryptophan was found to be among the metabolites with the 10 highest VIP scores. Pearson's correlation analysis showed that kynurenine and tryptophan were positively correlated only in subjects with the rs9939609 A allele ( = 32, = 0.56, < 0.001) and the correlation coefficients were significantly higher in subjects having the A allele than in those without the A allele ( < 0.05). Moreover, the kynurenine/tryptophan ratio was significantly associated with the presence of the A allele, independently of body mass index and sex. The FTO gene is likely to influences the conversion of tryptophan to kynurenine.